2019
DOI: 10.37358/mp.20.2.5370
|View full text |Cite
|
Sign up to set email alerts
|

Ether-Based Polyurethane Foam for Vacuum-Assisted Closure (V.A.C.) of Complicated Postoperative Abdominal Wound Dehiscence

Abstract: Background. The macroporous polyurethane ether foam was introduced in the medical field, as early as the 90 ties, for the Vacuum-assisted closure (V.A.C.) of a wound. We describe our experience after treating abdominal wound dehiscence in a group of elderly gynecological patients with NPWT (Negative Pressure Wound Therapy), using ether foam coated with a silver layer. We reviewed elderly patients chart data that underwent abdominal surgery complicated with wound dehiscence treated with VAC for eightee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 87 publications
(93 reference statements)
0
2
0
Order By: Relevance
“…Negative pressure reduces the fluid accumulation and the frequency of dressing changes to every 3-5 days (37). Although there are reports that VAC does not reduce the bacterial bioburden, most cases treated this way healed without incidents potentially because the foam reacts similar to a foreign body and generates an inflammatory reaction in the surgical site, and fails to reduce the extent of bacterial colonization (38)(39)(40).…”
Section: Surgical Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Negative pressure reduces the fluid accumulation and the frequency of dressing changes to every 3-5 days (37). Although there are reports that VAC does not reduce the bacterial bioburden, most cases treated this way healed without incidents potentially because the foam reacts similar to a foreign body and generates an inflammatory reaction in the surgical site, and fails to reduce the extent of bacterial colonization (38)(39)(40).…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…A previous study has suggested that VAC therapy speeds up the wound healing process and decreases the risk of wound complications (41). Previous studies reported a reduction of SSI incidence in several surgical fields when using VAC therapy compared with standard dressings when used on a closed surgical incision (5,40). In 2016, the World Health Organization (WHO) recommended negative pressure wound therapy on clean closed incisions as an innovative measure in high-risk patients for SSI with marked clinical results (42).…”
Section: Surgical Techniquesmentioning
confidence: 99%